2017
DOI: 10.1536/ihj.16-129
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Procedural Risk Score of Contrast-Induced Nephropathy in Elderly Patients Undergoing Elective Coronary Angiography

Abstract: SummaryTo establish a scoring model to predict the risk of contrast-induced nephropathy (CIN) in elderly patients undergoing elective coronary angiography (CAG).A total of 1286 patients aged > 65 years who had undergone elective CAG between August 2009 and February 2013 were enrolled in this study. They were randomly (3:2) assigned to a development (n = 756) or validation dataset (n = 530). Independent predictors of CIN were identified by using logistic regression and were assigned a weighted integer, which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 23 publications
5
20
0
Order By: Relevance
“…14,15,21) Our results verified this approach by showing that the attenuation of images at 40-60 keV monoenergetic spectral levels are at least comparable or even higher than with the use of 100 kVp, which has been illustrated in Figure 1. Since chronic renal insufficiency and kidney disease are very common among patients with CAD, 22,23) this significant reduction in iodine load could enormously benefit patients with borderline renal function and increased risk of contrast-induced nephropathy, 24) which has been increasingly discussed and widely recognized. 14,15,25) Multiple studies have demonstrated DECT's expanded role in providing a more comprehensive cardiac assessment.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,21) Our results verified this approach by showing that the attenuation of images at 40-60 keV monoenergetic spectral levels are at least comparable or even higher than with the use of 100 kVp, which has been illustrated in Figure 1. Since chronic renal insufficiency and kidney disease are very common among patients with CAD, 22,23) this significant reduction in iodine load could enormously benefit patients with borderline renal function and increased risk of contrast-induced nephropathy, 24) which has been increasingly discussed and widely recognized. 14,15,25) Multiple studies have demonstrated DECT's expanded role in providing a more comprehensive cardiac assessment.…”
Section: Discussionmentioning
confidence: 99%
“…4) Various methods for preventing CIN have been reported, including hydration, hemofiltration, intravenous administration of iloprost, and the use of ascorbic acid, nicorandil, or N-acetylcysteine. [5][6][7][8][9][10][11][12][13][14] However, there is presently no gold standard method and CIN occurs in approximately 5%-18.5% of patients, even when preventive methods are applied. The most effective method to prevent CIN is contrast volume reduction 15) .…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the dangers, many previous studies have used over 100 mL of iodinated contrast medium, except when performing carbon dioxide angioplasty. [5][6][7][8][9][10][11][12][13][14] EVT can be performed effectively with carbon dioxide angioplasty in CKD patients. 16,17) However, this method is associated with severe complications and poor image quality.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we excluded 11 post-procedure risk scores for CI-AKI according to our goals [18][19][20][21][22][23][24][25][26][27][28], and due to lack of C-reactive protein data, the Athens score was excluded [29]. We ultimately included 8 preoperative risk scores for CI-AKI in the final validation analysis [30][31][32][33][34][35][36][37].…”
Section: Overview Of Risk Scoresmentioning
confidence: 99%